Balancing operational efficiency and service quality : how strategy shapes performance in the US airline industry - Parast, Mahour; Golgeci, Ismail; Golmohammadi, Davood (Emerald, 2025)
Purpose – We examine how operational efficiency (OE) and service quality (SQ) interact to influence profitability, contingent on a firm’s strategic orientation (SO), whether focused or non-focused. Our study introduces a new perspective linking OE, SQ and profitability through competitive priorities and the moderating role of SO. Design/methodology/approach – Using US airline panel data, we employ econometric analyses and robustness checks, including alternative model specifications, to validate our hypotheses and ensure result reliability. Findings – We find that different dimensions of OE interact with SQ in varying ways to influence profitability. For both OE measures, their interaction with SQ negatively affects profitability, aligning with theoretical expectations, although the effects are not statistically significant. These results suggest potential contingency factors shaping this relationship. Furthermore, a firm’s SO moderates the OE–SQ–profitability link. The effects are positive as hypothesized, with SO particularly moderating the interaction between labor productivity and SQ, indicating that aligning SQ and productivity with SO enhances performance. Originality/value – Our research addresses conflicting findings in the literature regarding the relationship between OE, SQ and firm performance by demonstrating the moderating effect of a firm’s SO on this relationship. Our approach, examining the interaction between various measures of OE and SQ with profitability, offers a more value-driven and managerially focused perspective. The findings suggest that the effectiveness of balancing OE and SQ to drive profitability is contingent on the firm’s SO.
Keywords: Operational efficiency; Service quality; Operations strategy; Strategic orientation; Profitability; fi=Kansainvälinen liiketoiminta|en=International Business|